Forecasting Inflation in Egypt (2019-2022) by using AutoRegressive Integrated Moving Average (ARIMA) Models - Mohamed A. Omar; Shahin, Sara. E.; Magdy Roshdy (Journal of Advanced Veterinary Research, 2022)
The ARIMA model was employed to investigate annual inflation rates in Egypt from 2018 to 2022. The study planned to forecast inflation in Egypt for the upcoming period from August till December of 2022, and the best fitting model was carefully selected based on the minimum AIC value. ARIMA model was applied using EViews10. It is made up of three processes: the Autoregressive process (AR), the differencing process (d), and the Moving Average Process (MA). The Box–Jenkins methodology for analyzing and modeling time series is characterized by four steps: model identification, parameter estimation, diagnostic checking and forecasting. This study used Autoregressive Integrated Moving Average (ARIMA) model to estimate and forecast the inflation rates for the year 2018-2022 using the univariate historical data of inflation rate. The ARIMA (1, 1, 1) model is stable and most suitable model to forecast inflation in Egypt for the next five months. The percent value of the inflation in August is (11.4± 4.20); September (10.6±4.13); October (10.0±4.03); November (9.5± 4.23) and December (9.2± 4.11). In order to reduce inflation and increase macroeconomic stability in Egypt, policymakers should continue to implement sound economic policies.